CONTROL OF SULFATE PORE-WATER PROFILES BY SEDIMENTARY EVENTS AND THE SIGNIFICANCE OF ANAEROBIC OXIDATION OF METHANE FOR THE BURIAL OF SULFUR IN MARINE SEDIMENTS - Hensen C.; Zabel M.; Pfeifer K.; Schwenk T.; Kasten S.; Riedinger N.; Schulz H.D.; Boetius A. (My University, 2003)
Gravity driven mass-flow deposits proven by sedimentary and digital echosounder data are indicative for prevailing dynamic sedimentary conditions along the continental margin of the western Argentine Basin. In this study we present geochemical data from a total of 23 gravity cores. Pore-water SO4 is generally depleted within a few meters below the sediment surface by anaerobic oxidation of methane (AOM). The different shapes of SO4 profiles (concave, kink- and s-type) can be consistently explained by sedimentary slides possibly in combination with changes in the CH4 flux from below, thus, mostly representing transient pore-water conditions. Since slides may keep their original sedimentary signature, a combined analysis and numerical modeling of geochemical, physical properties, and hydro acoustic data could be applied in order to reconstruct the sedimentary history. We present first order estimates of the dating of sedimentary events for an area where conventional stratigraphic methods failed to this day. The results of the investigated sites suggest that present day conditions are the result of events that occurred decades to thousands of years ago and promote a persisting mass transport from the shelf into the deep-sea, depositing high amounts of reactive compounds. The high abundance of reactive iron phases in this region maintains low hydrogen sulfide levels in the sediments by a nearly quantitative precipitation of all reduced sulfate by AOM. For the total region we estimate a SO4 (or CH4) flux of 6.6 x 1010 moles per year into the zone of AOM. Projected to the global continental slope and rise area, this may sum up to about 2.6 x 1012 moles per year. Provided that the sulfur is completely fixed in the sediments it is about twice the global value of the recent global sulfur burial in marine sediments of 1.2 x 1012 moles per year as previously estimated. Thus, AOM obviously contributes very significantly to the regulation of global sulfur reservoirs, which is hitherto not sufficiently recognized. This finding may have implications for global geochemical models, as sulfur burial is an important control factor in the development of atmospheric oxygen levels over time.